Cardiac autonomic modulation impairments in advanced breast cancer patients - Arab, Claudia; Vanderlei, Luiz Carlos Marques; da Silva Paiva, Laércio; Fulghum, Kyle Levi; Fristachi, Carlos Elias; Nazario, Afonso Celso Pinto; Elias, Simone; Gebrim, Luiz Henrique; Ferreira Filho, Celso; Gidron, Yori; Ferreira, Celso (My University, 2018)
Aim: To compare cardiac autonomic modulation in early- versus advanced-stage breast cancer patients before any type of cancer treatment and investigate associated factors. Methods and results: This cross-sectional study included women (30–69 years old) with primary diagnosis of breast cancer and women with benign breast tumors. We evaluated cardiac modulation by heart rate variability and assessed factors of anxiety, depression, physical activity, and other relevant medical variables. Patients were divided into three groups based on TNM staging of cancer severity: early-stage cancer (n = 42), advanced-stage cancer (n = 37), or benign breast tumors to serve as a control (n = 37). We analyzed heart rate variability in time and frequency domains. The advanced-stage cancer group had lower vagal modulation than early-stage and benign groups; also, the advance-stage group had lower overall heart rate variability when compared to benign conditions. Heart rate variability was influenced by age, menopausal status, and BMI. Conclusions: Heart rate variability seems to be a promising, non-invasive tool for early diagnosis of autonomic dysfunction in breast cancer and detection of cardiovascular impairments at cancer diagnosis. Cardiac autonomic modulation is inversely associated with breast cancer staging.
Keywords: Autonomic nervous system; Breast tumor; Cardiology; TNM classification